BONDING CHARACTERISTIC OF GAMBIR TANNIN-BASED ADHESIVE ON TUSAM WOOD (Pinus merkusii) IN VARIOUS AGES : EFFECTS OF GAMBIR LEAVES CONDITION AND EXTENDER ADDITION - Adi Santoso; Erlina Nurul Aini; Dina Alva Prastiwi (Masyarakat Peneliti Kayu Indonesia, 2022)
Exploration of natural wood adhesive as an alternative to conventional adhesives such as UF and PF is an interesting topic to be investigated further due to the increasing of human awareness on environmental sustainability and health. Among several types of natural adhesives, tannin-based adhesive is considerably potential to be developed as commercial wood adhesive. In Indonesia, one of the material that has high potential as a raw material for making tannin-based adhesives is gambir leaves. In this study, the effect of leaf freshness, extender content and wood age were studied on the quality of the laminated product. The results showed that all three factors have a significant effect on the compressive shear strength of the laminated wood. The condition of fresh leaves, 0% extender content and 27 years old wood produced a laminated product with the highest compressive shear strength. All laminated wood products in this study meet the compressive shear strength requirement of SNI standards. Moreover, all laminated wood glued using tannin adhesive from fresh leaves without addition of extender are also able to meet the JAS standard requirement of compressive strength. The research results also show that gambir tannin adhesive has properties and bonding strength that can compete with PF adhesive. From these results, we can conclude that gambir tannin-based adhesive demonstrates an ability to serve as an alternative for conventional adhesive commonly used in wood industry.